Análisis jurídico y comparado respecto al Síndrome de Alienación Parental en Legislación Ecuatoriana - Ordoñez Tigre, Yoleydy Mickaela (2024)
This research project presents a doctrinal, legal and comparative analysis of Parental Alienation Syndrome in Ecuadorian legislation. Although there is no specific law in Ecuador that directly covers this syndrome, judicial decisions have recognised its existence and taken it into account when determining child arrangements. Nevertheless, there is no established legal framework for this issue. Parental alienation syndrome typically occurs in the context of parent- child relationships, particularly in highly contentious separations or divorces. In such cases, the aim is to assess whether a parent has psychologically manipulated the child from the other parent. From a comparative perspective, the study identified references to legislation in other countries. For example, Argentina has introduced criminal liability for parents who prevent direct and regular contact with the other parent. In Ecuador, although there is no specific legislation on PAS, the judiciary has recognised its existence and taken it into account in decisions on child custody and guardianship. Therefore, it is important that cases of PAS are assessed on an individual basis, prioritizing the best interests of the child and ensuring that their rights are protected. It is important to emphasize that this research project includes a comprehensive analysis of legal information from descriptive, evaluative, explanatory and prospective perspectives within the legal framework of children's rights. The study uses appropriate methodologies and materials to facilitate its development. In addition, interviews and surveys are conducted with legal professionals to promote a critical perspective on Parental Alienation Syndrome and its impact on the overall development of children and their best interests.